Paradigmas y polifuncionalidad Estudio diacrónico de «preciso»/«precisamente», «justo»/«justamente», «exacto»/«exactamente» y «cabal»/«cabalmente» - Gerhalter, Katharina (Beihefte zur Zeitschrift für romanische Philologie, 2020)
This study presents a corpus-based semasiologial and onomasiological analysis of the paradigm of adjectives and adverbs of accuracy. Looking specifically at justo / justamente, cabal / cabalmente, preciso / precisamente, and exacto / exactamente, it is above all concerned with the development of three pragmatic-discursive functions: focalization, affirmation, and reformulation.